The prospects for pharmacotherapy of disorders of venous outflow and microcirculation in chronic venous disease. Based on the consensus of the international union of phlebology (UIP) - V. Y. Bogachev; B. V. Boldin; S. V. Rodionov; O. V. Dzhenina (Амбулаторная хирургия)
Chronic venous diseases (CVDs) represent the most common pathology of peripheral vessels, the development of which involves different patho-genetic mechanisms leading to functional and structural abnormalities of the venous and lymphatic system of the lower extremities. One of the current trends in the correction of different stages and forms of CVD is pharmacological therapy which prioritizes the use of phlebotropic drugs (syn.: phleboprotectors, venoactive drugs (VADs)). The review summarizes the most recent data concerning the effect of phlebotropic drugs on macro- and microhemodynamics of CVDs.